COMPULSORY EDUCATION DAN SISTEM PEMBIAYAAN PENDIDIKAN SERTA KONSEP PENDIDIKAN GRATIS DALAM ISLAM - Muhammad Ruslan (Jurnal Al-Fatih, 2021)
This article discusses compulsory education and education financing systems in Indonesia. The discussion uses manuscript studies. The compulsory education concept approach describes the basis of laws that regulate the right to universal education. One of the laws that govern this problem is the National Education System Law No. 20 of 2003 that, "Compulsory education is a minimum education program that must be followed by Indonesian citizens on the responsibility of the Government and Local Government" The State is obliged to ensure that students continue to go to school by providing tuition assistance. But the fact is that there are still many children who drop out of schooll. This article offers a solution to the problem of education costs by maximizing the government's responsibility to complete the 12 year compulsory education program. Based on APK and APM, it becomes a reference for effective and efficient work steps to allocate appropriate education funds. In the author's analysis, the compulsory education program in Indonesia is different from the compulsory education model in developed countries. This shows that there are no legal sanctions for parents who do not send their children to school. The cost of education that is borne by the State of Indonesia is more directed towards direct costs, while in developed countries the cost of education has been allocated to direct costs and indirect costs